Videolibras: Multimedia authoring and broadcasting system to allow libras window on the Brazilian ODTV - Dos Santos, Edson Benedito [UNESP]; Oliveira, Hilda Carvalho [UNESP]; Oliveira, Celso Socorro [UNESP] (My University, 2014)
Presently there are 24.6 million of the people with special needs in Brazil, with 23% having some type of hearing loss and 2.9% of these deaf. The Accessibility Brazilian Law establishes that the accessibility of services for the deaf shall be provided by interpreters or people trained in Brazilian Sign Language (LIBRAS). Brazilian Laws provides that the teaching of LIBRAS must be part of the curriculum of all courses in Special Education, Speech Therapy and Magisterium at high school and college courses. This paper presents VideoLIBRAS, a authoring, broadcasting and control system to contribute to the growing demand in learning Brazilian Sign Language (LIBRAS), providing flexibility of building the content for teaching-learning of LIBRAS through subtitled videos and windows with LIBRAS interpreters. Contents can be prepared in accordance with the need and suitability for in-class, without requiring Informatics specialists. This content is automatically converted to be viewed in Web environments and in environments that use the standard Ginga- NCL, such as IPTV and Open Digital TV (ODTV) in Brazil. The window with the recording of the LIBRAS interpreter (LIBRAS window) is controlled by the user and can be hidden or adjusted in size and position. The work was guided by the law and Brazilian Technical Standards.
Keywords: Accessibility; Deaf; Digital TV; E-learning; Ginga; Libras